The study on factor that may influence credit risk management knowledge and awareness among micro business in Malaysia - Mohamad Yazis Ali Basah; Hisham Sabri; Khairil Faizal Khairi; Mahdhir Abdullah; Mazlynda Md Yusuf; Muhamad, Nur Masitah (Medwell Journals, 2024)
Indexed by SCOPUS